Conserto Opus 3 No 6 by Antonio Vivaldi: An Overview of Forms of Ritornello and Music Construction - Ance Juliet Panggabean; Franky Fransisko Hutahaean; Bintang Hadi Putra Saragih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research aims at analyzing Concerto Opus 3 No. 6 by Antonio Vivaldi in terms of Ritornello's form and musical construction. The basic method applied in this research is descriptive. Besides that, the approach method used is the library method so that it is found and produced Ritornello Form Analysis and Musical Construction. Through Analysis of Concerto Opus 3 No 6 by Antonio Vivaldi Viewed From Ritornello's Form and Construction Vivaldi's concerto music which is famous for its string music characteristics, regarding the form and pattern of its structure as well as the parts contained in the construction of the music, the beginning, the continuation part, the complication part and the resolution section. In addition to his musical constructions, Vivaldi's concerto uses Ritornello and Episode patterns which are brilliant in Baroque terms. With the use of chord levels (harmony progressions) and soloist and tutti (orchestral) playing, this concerto was more solemn and majestic for its time.